Pengembangan Modul Keanekaragaman Genetik Jagung Lokal Gorontalo Untuk Pembelajaran Biologi SMA: (Development of a Genetic Diversity Module for Gorontalo Local Corn for High School Biology Learning) - Hidayat, Ahmad; Kandowangko, Novri Youla; Latjompoh, Masra; Katili, Abubakar Sidik; Pagalla, Devi Bunga (BIODIK, 2025)
The lack of contextual teaching materials that highlight local potential is a challenge in biology learning in schools. This study aims to determine the validity and practicality of the learning module on genetic biodiversity in local Gorontalo corn plants. This study uses the Research and Development method. The learning module was developed using the ADDIE model, up to the limited trial stage. The research subjects were 25 grade X high school students. The learning module was validated by material experts and media experts, and the practicality of using the module in learning biodiversity material was tested. The validation results showed that the module was very valid with an average percentage of 98% from material experts and 93.77% from media experts. The practicality of the module was also very high based on teacher responses of 97.77% and student responses of 98.06%. From the results of the validity and practicality tests, it can be concluded that the learning module on genetic biodiversity in local corn plants can be used in learning Biology for grade X high school, biodiversity material in schools. Abstrak. Kurangnya bahan ajar kontekstual yang mengangkat potensi lokal menjadi tantangan dalam pembelajaran biologi di sekolah. Penelitian ini bertujuan untuk mengetahui validitas dan kepraktisan modul pembelajaran keanekaragaman hayati tingkat genetik pada tanaman jagung lokal Gorontalo. Penelitian ini menggunakan metode Research and Development.  Modul pembelajaran dikembangkan dengan menggunakan model ADDIE, hingga tahapan uji coba terbatas. Subjek penelitian adalah 25 peserta didik kelas X SMA. Modul pembelajaran divalidasi oleh ahli materi dan ahli media, serta diuji kepraktisan penggunaan modul dalam pembelajaran materi keanekaragaman hayati.  Hasil validasi menunjukkan bahwa modul sangat valid dengan rata-rata persentase 98% dari ahli materi dan 93,77% dari ahli media. Kepraktisan modul juga sangat tinggi berdasarkan respons guru sebesar 97,77% dan respons peserta didik sebesar 98,06%. Dari hasil uji validitas dan kepraktisan, maka dapat disimpulkan bahwa modul pembelajaran keanekaragaman hayati tingkat genetik pada tanaman jagung lokal dapat digunakan dalam pembelajaran Biologi kelas X SMA, materi  keanekaragaman hayati  di sekolah.